A Case of Ovarian Actinomycosis - Masahiro Iwasaki; Akira Nishikawa; Noriyuki Akutagawa; Takashi Fujimoto; Mizue Teramoto; Ryuichi Kudo (Hindawi Limited, 2003)
Background: Pelvic actinomycosis is uncommon and often presents as a complication of an intrauterine device (IUD). A diagnosis of actinomycosis can be made from the finding of sulfur granules within inflammatory exudate on histologic examination after surgery. However, it may be possible to diagnose actinomycosis before surgery by finding Actinomyces-like organisms on Papanicolaou smears.